Lithuanian spoken corpora and studies of first language acquisition: a view from outside - Riekhakaynen, Elena (Lietuvių kalba, 2019)
The paper provides an overview of Lithuanian spontaneous speech corpora and certain studies of the acquisition of Lithuanian as a first language. The author focuses mainly on those resources and papers that are published in English and thus can be used by non-Lithuanian speaking researchers as methodological and/or theoretical inspiration for further studies on different languages. Among the spoken corpora discussed in the paper are: the speech corpus Liepa, Sakytinės kalbos įrašų bazė, the Corpus of Spoken Lithuanian. The author pays special attention to the latter as it is closely connected to the development of the Lithuanian corpus of child and child-directed speech. The studies of the acquisition of Lithuanian as a first language are overviewed in the second part of the paper. The majority of studies on corpus data (including those conducted within international cross-linguistic projects) describe the acquisition of grammar by native speakers of Lithuanian. In the most recent research, there is a shift towards new aspects of first language acquisition (including phonology and morphophonology) and new methods (experiments becoming more and more popular).
Keywords: spoken corpora; spontaneous speech; first language acquisition; Lithuanian; Russian